Sistem Kendali Irigasi Otomatis Pada Pertanian Hidroponik Vertikal Berbasis Internet Of Things (IoT) - Permata Sari, Dewi; Dewi Permata sari; RD. Kusumanto; Mardiyansah (Indonesian Society of Applied Science (ISAS), 2023)
Vertical hydroponic farming is an innovative method of cultivating plants efficiently in urban environments. However, the main challenge in managing hydroponic farming is monitoring and regulating appropriate water levels for plants, especially on a large scale or in remote locations. To overcome this problem, an automatic irrigation control system based on the Internet of Things (IoT) is a potential solution. This study proposes the development of an automatic irrigation control system integrated with IoT technology to increase the efficiency and productivity of vertical hydroponic farming. This system consists of ultrasonic sensors and water flow sensors which are connected directly to a microcontroller, which is then connected to the IoT platform via a wireless network. Data obtained from these sensors is sent to the IoT platform for processing and analysis in real-time.